Expression characteristics of β-catenin in scallop Chlamys farreri gonads and its role as a potential upstream gene of Dax1 through canonical Wnt signalling pathway regulating the spermatogenesis. - Hailong Li; Zhifeng Zhang; Ying Bi; Dandan Yang; Litao Zhang; Jianguo Liu (PLoS ONE, 2014)
β-catenin is a key signaling molecule in the canonical Wnt pathway, which is involved in animal development. However, little information has been reported for β-catenin in bivalves. In the present study, we cloned a homolog of β-catenin from the scallop Chlamys farreri and determined its expression characteristics. The full-length cDNA of β-catenin was 3,353 bp, including a 2,511 bp open reading frame that encoded a predicted 836 amino acid protein. Level of the β-catenin mRNA increased significantly (P<0.05) with C. farreri gonadal development and presented a sexually dimorphic expression pattern in the gonads, which was significantly high in ovaries detected by quantitative real-time polymerase chain reaction (qRT-PCR). Immunohistochemical analysis revealed that the β-catenin was mainly located in germ cells of the gonads, with obvious positive immune signals in the oogonia and oocytes of ovaries as well as in the spermatogonia and spermatocytes of testes, implying β-catenin might be involved in the gametogenesis of C. farreri. Furthermore, when 0.1 µg/mL and 0.2 µg/mL DKK-1 (an inhibitor of the canonical Wnt pathway) were added in vitro to culture medium containing testis cells of C. farreri, the expression of β-catenin decreased significantly detected by qRT-PCR (P<0.05), suggesting the canonical Wnt signal pathway exists in the scallop testis. Similarly, when 50 µM and 100 µM quercetin (an inhibitor of β-catenin) were added in vitro to the culture system, Dax1 expression was significantly down-regulated compared with controls (P<0.05), implying the β-catenin is an upstream gene of Dax1 and is involved in the regulation of C. farreri spermatogenesis.